KERANGKA ISTINBATH MASLAHAH MURSALAH SEBAGAI ALTERNATIF PROBLEM SOLVING DALAM HUKUM ISLAM - Wahyu Abdul Jafar (Istinbath : Jurnal Hukum, 2016)
This study explains the importance of limits and rules in beristinbath using maslahah mursalah. Not all the reasons the benefit on any issue that can be accepted and relied upon in the beristinbath but still need the filtering process in advance. Only reasons that meets the requirements can be allowed to be used as proof in beristinbath using maslahah mursalah. This is important because if it is done in the beristinbath using the opportunities given mursalah maslahah as free-free without any clear rules, will dihawatirkan appear legal products which do not comply with maqosyid al-Shari'ah (Islamic law forming). Later in this study described the question of beristinbath framework using approach of maslahah mursalah in detail, beginning with the process description, collection and presentation of data related to issues that will be discussed. Then proceed with the process of verification and justification.